2007
DOI: 10.2471/blt.06.036764
|View full text |Cite
|
Sign up to set email alerts
|

Risk of arsenic-related skinlesions inBangladeshi villages at relatively low exposure: a report from Gonoshasthaya Kendra

Abstract: Objective Arsenic concentrations in 25% of tube wells in Bangladesh exceed 50μg/L, a level known to be hazardous. Levels in individual wells vary widely. We gathered data on arsenic exposure levels and skin lesion prevalence to address the lack of knowledge about risks where the average arsenic concentrations was lower. Methods The nongovernmental organization Gonoshasthaya Kendra did three related studies of keratotic skin lesions since 2004:(1) an ecological prevalence survey among 13 705 women aged > 18 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Third, the exposure assessment was limited; it was ecological in that it was based on measurements obtained on 50–70 wells per district. There is evidence of considerable variation in arsenic concentrations in wells within a district6 and the use of mean concentration as an estimate will result in misclassification of the exposure of many of those living within the region and a consequent underestimate of effect size. In addition, the data related to the current address rather than any previous one.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the exposure assessment was limited; it was ecological in that it was based on measurements obtained on 50–70 wells per district. There is evidence of considerable variation in arsenic concentrations in wells within a district6 and the use of mean concentration as an estimate will result in misclassification of the exposure of many of those living within the region and a consequent underestimate of effect size. In addition, the data related to the current address rather than any previous one.…”
Section: Discussionmentioning
confidence: 99%
“…With the emerging evidence of the negative health effects due to chronic low-doses of As (Chen et al, 2009; McDonald et al, 2007) as well as the presence of additional routes of exposure (Pal et al, 2007), primarily food (Kile et al, 2007; Roychowdhury et al, 2002), we must be proactive in setting protective guideline values and standards to safeguard not only currently at-risk populations but future generations (Raqib et al, 2009; Smith et al, 2006) and those currently suffering. Once the signs and symptoms of arsenicosis emerge, there is little treatment that can be provided other than symptomatic care.…”
Section: Methodsmentioning
confidence: 99%
“…These dermal effects have been noted in a large majority of human studies involving repeated oral exposure via arsenic-contaminated drinking water. Studies in Bangladesh (Ahsan et al, 2000Rahman et al, 2006a;McDonald et al, 2007), India (Guha Mazumder et al, 1998;Haque et al, 2003), Inner Mongolia Li et al, 1994;Luo et al, 1994;Sun et al, 1994;Yoshida et al, 2004;Guo et al, 2006;Xia et al, 2009) and Pakistan (Fatmi et al 2009;Kazi et al, 2009) reported increased incidences of skin lesions associated with arsenic concentrations in drinking water <100 µg/L.…”
Section: Skin Lesionsmentioning
confidence: 99%